Pendampingan dan Sosialisasi Pembuatan Lapak Online Berbasis Digital Marketing untuk Meningkatan Pendapatan Pedagang Pasar Sunan Drajat Lamongan - Setyowati, Suci Yongki; Ismiasih, Novi; Mustika, Tito Nur (Fakultas Ekonomi dan Bisnis Islam Institut Pesantren Sunan Drajat Lamongan, 2023)
Sunan Drajat Lamongan Traditional Market is a market with a relatively large number of traders. This market provides various kinds of needs, from household needs, typical Lamongan souvenirs, and etc. However, along with the rapid development of technology, some traders are experiencing difficulties due to the proliferation of online markets circulating in the trading world. Traders stated that now the profit they get is not what it used to be. This is because consumers prefer to shop through digital marking(online markets). Therefore, the team of lecturers at the Sunan Drajat Islamic Boarding School Institute held socialization and assistance in the digital marketing sector, especially the creation of online stalls for Sunan Drajat Lamongan market traders. This activity aims to help traders compete in this digital marketing era. Apart from that, this activity also helps traders to improve and expand the marketing reach of their products through creating online stalls. From this activity, 10 traders have received socialization and assistance regarding creating online shop and how to operate them. In the monitoring carried out, the activity of creating online shop was apparently able to increase the income of traders. Within 2 weeks after the operation of the online shop that had been created, majority traders stated that they received additional income from buyers' orders through the online shop. This is in line with the aim of holding this activity.